On Design Autonomic Behavior for Blockchain platforms - Freitas, Allan Edgard Silva (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Companion Proceedings of the 12th Latin-American Symposium on Dependable Computing, 2023)
This paper explores the potential for improving blockchain performance through the implementation of an adaptive consensus machine. Blockchains, as immutable distributed ledgers, have found applications in various domains such as cryptocurrency, supply chains, healthcare, and more. The two main types of blockchains are permissionless and permissioned, each with its own advantages and limitations. The proposal suggests monitoring transaction metrics on the blockchain to enable the adaptive machine to adjust operational parameters of the consensus protocol or even switch to a different consensus strategy. This autonomic approach aims to enhance the overall performance of the blockchain by utilizing self-defined policies and goals. The paper discusses the use of off-chain structures for recording transactions and the trade-offs between latency and cost. Furthermore, it highlights the potential improvements that can be achieved by adapting classic consensus algorithms in permissioned blockchains. By incorporating adaptive and autonomic techniques, blockchain platforms can achieve enhanced efficiency and performance.